Teachers Learn and Learners Teach: Enacting Presence in Online Havruta Text Study. Issue 4 (2nd October 2021) - Gold, Mindy M.; Raider-Roth, Miriam; Holzer, Elie
ABSTRACT: In the wake of COVID, the Mandel Teacher Educator Institute (MTEI) faced essential pedagogical challenges in creating learner-centered, relational, and inquiry-based Jewish text study in an online synchronous space. In fall 2020, we offered an online adaptation of a line-by-line method for text study to understand the way this pedagogy invites enactments of teaching, social, and cognitive presences. This study uses qualitative methodologies to understand the learners' experiences. Implications from this study can help us understand how activating presence in online spaces can bring rich, connected Jewish learning experiences into spaces often perceived to be flat and disconnected.